Evaluación de la viabilidad técnico-financiera de las nanopartículas de sílice como aditivo para el control del filtrado en el fluido de perforación base agua a nivel laboratorio (2017)
In this project Nanosilica in the aqueous phase is evaluated as a filtering controller in the water based sludge from a series of laboratory tests in several stages, since this product had not previously been evaluated as an additive in the drilling fluid. In the first stage of laboratory tests the physical and chemical properties of Nanosilica in aqueous solution are evaluated. In the second phase of laboratory tests the above mentioned physical and chemical properties. In the third test phase, a performance comparison of the Nanosilica with respect to the starch-based and the polymer base-based controllers is performed with the formulation that has the best result with respect to the filtrate. In the fourth phase Nanosilica is evaluated at high temperature and high pressure conditions by performing a HP / HT and Permeation Capping (PPT).